Numerical investigation of MHD nanofluid free convective heat transfer in a porous tilted enclosure. Issue 6 (7th August 2017) - Sheikholeslami, M.
Abstract : Purpose: The effect of a magnetic field on nanofluid natural convection in a porous annulus is simulated. Control volume-based finite element method (CVFEM) is applied to find the influence of tilted angle and Darcy, Rayleigh and Hartmann numbers on nanofluid hydrothermal behavior. Vorticity stream function formulation is taken into account. Also, Brownian motion effect on nanofluid thermal conductivity is considered. Results reveal that Hartmann number and tilted angle make changes in nanofluid flow style. Nusselt number enhances with augment of Darcy number and buoyancy forces but reduces with rise of tilted angle and Hartmann number. Design/methodology/approach: The influence of adding CuO nanoparticles in water on the velocity and temperature distribution in an inclined half-annulus was studied considering constant heat flux. CVFEM is applied to the simulation procedure. Findings: Influences of CuO volume fraction, inclination angle and Rayleigh number on hydrothermal manners are presented. Originality/value: Results indicate that inclination angle makes changes in flow style. The temperature gradient enhances with rise of buoyancy forces, whereas it reduces with augment of inclination angle.